2020
DOI: 10.1080/15538362.2020.1784075
|View full text |Cite
|
Sign up to set email alerts
|

Mulberries: A Promising Fruit for Phytochemicals, Nutraceuticals, and Biological Activities

Abstract: The review highlights the significance of mulberry fruits in both chemical and biological sagacity and their role as antioxidant, anticancer, antidiabetic, hepatoprotective, neuroprotective, anti-inflammatory, antiobesity, hypolipidemic, and antibacterial. Besides, having phytochemicals induced biological pathways and nutritional value. Although a number of mulberry fruits species available in nature, the review elucidates the specific role of Morus alba, Morus nigra, Morus rubra, whose functions in living sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…The micro-organism used were Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Bacillus subtilis. There was no antibacterial activity observed in the agar well diffusion with Escherichia coli and the MIC assay [21][22][23][24][25][26][27][28][29]. The antioxidant activity of the plant extract was assessed through the method of DPPH test while the total amount of phenolic compounds in the extract can be determined through the TPC test.…”
Section: Discussionmentioning
confidence: 99%
“…The micro-organism used were Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Bacillus subtilis. There was no antibacterial activity observed in the agar well diffusion with Escherichia coli and the MIC assay [21][22][23][24][25][26][27][28][29]. The antioxidant activity of the plant extract was assessed through the method of DPPH test while the total amount of phenolic compounds in the extract can be determined through the TPC test.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in Korea and Japan, patients with diabetes consume mulberry leaves as an anti-hyperglycemic supplement [ 35 ], and the leaves are known to be effective against high blood pressure and hangover from alcohol and in lowering blood sugar levels related to diabetes [ 36 ]. Previous biological studies of M. alba have reported that its extracts exhibit diverse therapeutic properties, including antioxidant, antimicrobial, skin-whitening, cytotoxicity, anti-inflammatory, anti-hyperlipidemic, hepatoprotective, antidiabetic, and anti-obesity effects [ 37 , 38 ]. In addition, previous phytochemical studies on M. alba have demonstrated the presence of diverse chemical constituents including terpenoids, alkaloids, flavonoids (including chalcones and anthocyanins), phenolic acids, stilbenoids, and coumarins [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous biological studies of M. alba have reported that its extracts exhibit diverse therapeutic properties, including antioxidant, antimicrobial, skin-whitening, cytotoxicity, anti-inflammatory, anti-hyperlipidemic, hepatoprotective, antidiabetic, and anti-obesity effects [ 37 , 38 ]. In addition, previous phytochemical studies on M. alba have demonstrated the presence of diverse chemical constituents including terpenoids, alkaloids, flavonoids (including chalcones and anthocyanins), phenolic acids, stilbenoids, and coumarins [ 38 ]. However, few previous studies have investigated the chemical constituents of M. alba with antidiabetic or anti-obesity effects and their underlying mechanisms of action, despite many studies on the pharmacological effects of M. alba extracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its fruit is a multiple fruit with a sweet flavor, and it is extensively consumed in various forms including as tea, dessert, and beverages worldwide [ 7 ]. Specifically, the mulberry fruit, which is rich in beneficial nutrients, contain secondary metabolites that have pharmacological activities such as antidiabetic, antioxidant, anti-obesity, and anti-inflammatory effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%